The Role of Islam In The Development Of Cultures - Ibodullayeva Shoira Dilshod Qizi (Indonesian Culture and Religion Issues, 2025)
This study explores the relationship between Islam and culture, highlighting how Islamic principles shape cultural traditions while allowing diversity among Muslim communities. The research aims to analyze the impact of Islam on cultural practices and the boundaries set by Islamic teachings regarding traditions that may contradict religious values. Using qualitative research methods, including literature review and historical analysis, the study examines key concepts such as culture, tradition, and secularism. The findings reveal that while Islam provides a unified religious framework through the Qur'an and Sunnah, cultural expressions vary across regions, influenced by history, geography, and societal norms. The study also discusses secularism’s impact on Muslim communities, emphasizing the importance of maintaining religious and cultural identity amid global influences. Ultimately, the research concludes that Islam enriches culture rather than suppressing it, fostering unity while embracing diversity. Understanding the balance between Islamic principles and cultural traditions is crucial for preserving religious and cultural heritage in a modern, globalized world.